Understanding Beta-Lactam-Induced Lysis at the Single-Cell Level - Wong, Felix; Wilson, Sean; Helbig, Ralf; Hegde, Smitha; Aftenieva, Olha; Zheng, Hai; Liu, Chenli; Pilizota, Teuta; Garner, Ethan C.; Amir, Ariel; Renner, Lars D. (Frontiers in Microbiology, 2021)
\section{Introduction} Mechanical rupture, or lysis, of the cytoplasmic membrane is a common cell death pathway in bacteria occurring in response to β-lactam antibiotics. A better understanding of the cellular design principles governing the susceptibility and response of individual cells to lysis could indicate methods of potentiating β-lactam antibiotics and clarify relevant aspects of cellular physiology. Here, we take a single-cell approach to bacterial cell lysis to examine three cellular features-turgor pressure, mechanosensitive channels, and cell shape changes-that are expected to modulate lysis. We develop a mechanical model of bacterial cell lysis and experimentally analyze the dynamics of lysis in hundreds of single Escherichia coli cells. We find that turgor pressure is the only factor, of these three cellular features, which robustly modulates lysis. We show that mechanosensitive channels do not modulate lysis due to insufficiently fast solute outflow, and that cell shape changes result in more severe cellular lesions but do not influence the dynamics of lysis. These results inform a single-cell view of bacterial cell lysis and underscore approaches of combatting antibiotic tolerance to β-lactams aimed at targeting cellular turgor.